A novel Wolbachia ftsZ genotype in ’Candidatus Phytoplasma solani’ planthopper vector Hyalesthes obsoletus (Hemiptera: Fulgoromorpha: Cixiidae) associated with Convolvulus arvensis - Stojanović, Luka; Popov, Olivera; Stepanović, Jelena; Duduk, Bojan; Kosovac, Andrea (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
Hyalesthes obsoletus (Hemiptera: Fulgoromorpha: Cixiidae) is a pan-European polyphagous planthopper known as a significant vector of the plant pathogenic bacterium ‘Candidatus Phytoplasma solani’ (stolbur phytoplasma), which poses threats to various agricultural crops. A population of H. obsoletus associated with Convolvulus arvensis in Serbia was studied to investigate the presence and genetic diversity of Wolbachia, an endosymbiotic bacterium known for its promising biological control applications. Both insect-associated microorganisms, ‘Ca. P. solani’ and Wolbachia, were found in the assessed H. obsoletus population. The analyzed vector population had a ‘Ca. P. solani’ infection rate of 50%, while Wolbachia showed a high infection rate of 80%. Wolbachia presence displayed minimal variation across genders and was independent of individuals’ phytoplasma-infection status. Genotyping of the identified ‘Ca. P. solani’ strains revealed four previously described stamp genotypes (Rqg50/St1, Rqg31/St2, STOL/St4 and M5/St28). Notably, a single novel Wolbachia ftsZ genotype, designated WHo1, was found in the assessed H. obsoletus population, providing a valuable insight into the genetic diversity of Wolbachia endosymbionts within the Cixiidae family. Phylogenetic analysis demonstrated intricate relationships between WHo1 and other Wolbachia strains infecting hosts from diverse hemipteran suborders. Although Wolbachia-based strategies show promise for phytoplasma vector control, further research is needed to elucidate its potential interactions with ‘Ca. P. solani’ and its effects on vector reproduction and fitness.